Paper Clay Game (Paper Paper) On Motorcycle Development Smoother Age 4 Until 5 Years In Dharma Women Tosaren II Kindergarten Kediri - Riza Tsalatsatul Mufida; Maria Oktaviani Abu (Universitas STRADA Indonesia, 2018)
One effort to improve fine motor skills is the game of pulp. The purpose of this research is to know the effect of pulp game on the development of fine motor development of children 4 to 5 years. This study uses the research method